SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN PRIORITAS PERBAIKAN JALAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN LANGKAT - Rizki Yulidha Astari; Budi Serasi Ginting; Anton Sihombing (JSIK (Jurnal Sistem Informasi Kaputama), 2021)
Roads are facilities and infrastructure that are very important for our daily lives, because roads are a link between one place and another. It is the duty of the Public Works and Spatial Planning Office to be able to manage data from all damaged roads. However, in handling road repairs, the relevant agencies are often not on target because of errors in determining the priority order of road repairs. Therefore, in this study a decision support system was built using the Analytical Hierarchy Process (AHP) method which is expected to assist the Public Works and Spatial Planning Service in determining priorities for which roads to repair based on criteria, namely road conditions, road length, and road width. , road surface type and average daily traffic (lhr). From the calculation results obtained the highest ranking value, namely Jalan Sp. Paya Salib - Paya Salib Kec. Serapit (A6) with a value of 0.384, so that the road deserves to be a priority to get treatment in road repair first.